Coronary flow reserve is reduced in sarcoidosis. (September 2017) - Kul, Seref; Kutlu, Gonul Aciksari; Guvenc, Tolga Sinan; Kavas, Murat; Demircioglu, Kenan; Yilmaz, Yusuf; Yakar, Halil Ibrahim; Kanbay, Asiye; Boga, Sibel; Caliskan, Mustafa
Abstract: Background and aims: Sarcoidosis is a multisystem disease with frequent cardiac involvement, albeit manifest cardiac disease is rare. Though epicardial coronary arteries are not frequently involved, microvascular disease is rather common in both symptomatic and asymptomatic patients. The mechanism of microvascular involvement has not been elaborated yet. The aim of this study is to investigate coronary flow velocity reserve (CFVR) using transthoracic echocardiography in patients with sarcoidosis but without known atherosclerotic coronary artery disease or risk factors for atherosclerosis. Methods: A total of 40 patients with sarcoidosis and 42 healthy volunteers without any known medical conditions were enrolled prospectively. Diastolic peak coronary flow velocities were measured during rest and maximal hyperemia induced with adenosine. Results: Patients within the sarcoidosis group had significantly higher diastolic peak velocity at rest (29.5 ± 5.8 vs. 22.8 ± 3.2, p  < 0.01) but both the diastolic peak velocity during hyperemia (60.5 ± 18.2 vs. 68.9 ± 15.7, p  = 0.03) and CFVR (2.08 ± 0.57 vs. 3.03 ± 0.60, p  < 0.01) were lower compared to controls. Sarcoidosis was an independent predictor for low (≤2.0) CFVR (OR: 56.8, 95%CI: 6.1–531.7, p  < 0.001), along with age and systolic blood pressure. For patients with sarcoidosis, age and systolic blood pressure were independent predictors for a low CFVR. Conclusions: Despite a lack of known risk factors for atherosclerosis, patients with sarcoidosis had lower CFVR compared to healthy controls, thus suggesting a dysfunction in the coronary microvasculature. A reduced response to vasodilators suggests possible structural alterations of the myocardial microvasculature, rather than being secondary to microvascular spasm as suggested previously. Highlights: Coronary flow velocity reserve is reduced in sarcoidosis. Sarcoidosis was an independent predictor for low coronary flow velocity reserve, along with age and systolic blood pressure. Reduced response to vasodilators suggests possible structural alterations of the myocardial microvasculature in sarcoidosis.